HAFIS Enterprise / Muhammad Syafiq Suhaimi... [et al.] - Suhaimi, Muhammad Syafiq; Jakaria, Mohd Zahid Irfan; Samsudin, Muhamad Nor Asyraf; Ahmad Shafawi, Muhamad Helmi; Mohd Azmy, Ahmad Farhan (2020)
HAFIS are packaging metal straws manufactured by our own company. We chose to retail these products because of the increasing demand and in metal straw products in Malaysia. Since Malaysians are becoming more aware of the environmental problems, more of them are looking for metal straws to minimize the usage of plastic straws. Our product does not only the metal straw itself, it also includes the brush and the pouch with a high-quality packaging. The retail price of or products is RM 13 per unit. The price of the item is pretty affordable and pretty much similar to existing metal straw products by other distributor and to be honest even cheaper from all the high-end brands like P .M. Lee Sdn. Bhd. We believe that our product will able to attract customers' attention and will able to compete with the already established brands in the market. This is because our product is affordable and has additional value that interest customers. In the organizational structure of the HAFIS Enterprise, we have executive manager, administrative manager, operation manager, marketing manager, general manager and financial manager. We also will hire sales assistants, operation staffs, marketing personnel, and clerk to ensure the sales of our products will run smoothly and the packaging operation can be conducted efficiently with excellent marketing strategies planned out by the marketing team.